ROTEM diagnostic capacity for measuring fibrinolysis in neonatal sepsis. Issue 192 (August 2020) - Lampridou, Maria; Sokou, Rozeta; Tsantes, Andreas G.; Theodoraki, Martha; Konstantinidi, Aikaterini; Ioakeimidis, Georgios; Bonovas, Stefanos; Politou, Marianna; Valsami, Serena; Iliodromiti, Zoe; Boutsikou, Theodora; Iacovidou, Nicoletta; et al.
Abstract: Background: Hypofibrinolysis has been demonstrated in several studies in adult sepsis. Although fibrinolysis is an important and integral part of the hemostatic system, few data are available regarding its role in neonatal sepsis. Our purpose was to define fibrinolytic profiles across neonatal sepsis spectrum using rotational thromboelastometry (ROTEM). Material and methods: This study was performed in a Greek tertiary General Hospital during an 18 month-period and included 44 neonates with confirmed sepsis and 22 with suspected sepsis; 110 healthy neonates served as controls. Whenever sepsis was suspected, EXTEM and APTEM assays were performed, clinical findings and laboratory data were recorded. Results: Although most EXTEM parameters were significantly different among the 3 groups, Maximal Lysis (ML) and Lysis Index at 60 min (LI60) levels were similar ( p  = 0.11 and p  = 0.20, respectively). Hyperfibrinolysis, as defined by ROTEM parameters, did not significantly differ among the study populations ( p  = 0.41). On the contrary, fibrinolysis shutdown, defined as an EXTEM LI60 ≥98%, was more common in septic neonates than in healthy ( p  < 0.001) and neonates with suspected sepsis ( p  = 0.042). A weak to moderate correlation of LI60 and ML with mortality (Spearman rho = 0.43 and − 0.40, p  = 0.005 and 0.007, respectively) and SNAPE score (Spearman rho = 0.35 and − 0.33, p  = 0.02 and 0.03, respectively) was noticed in sepsis group. Conclusions: ROTEM, based on fibrinolytic parameters, showed a more frequent fibrinolysis shutdown in neonatal sepsis, but it could neither effectively discriminate septic neonates, nor predict their clinical outcome. The considerable overlap among numerical ROTEM values probably compromises their diagnostic clinical utility in neonatal sepsis. Highlights: Fibrinolysis shutdown is frequently noted in neonatal sepsis by ROTEM assay. ROTEM reveals an intense hypocoagulable profile in neonatal sepsis. Numerical ROTEM values overlap compromises its clinical utility in neonatal sepsis.